Battling eight giants basic income now - Standing, Guy 1948- (I.B. Tauris, 2020)
"Today in one the richest countries in the world, 60% of households in poverty have people in jobs, inequality is the highest it has been for 100 years, climate change threatens our extinction and automation means millions are forced into a life of precarity. The solution? Basic Income. Here, Guy Standing, the leading expert on the concept, explains how to solve the new eight evils of modern life, and all for almost zero net cost. There is a better future, one that makes certain all citizens can share in the wealth of the modern economy. Far from being a new idea, Standing shows how the roots of basic income go back to the Charter of the Forest, one of two foundational documents of the state ? the other, sealed on the same day, being the Magna Carta. All citizens have a right to the wealth created by capitalism, and all - left or right, rich or poor - can benefit from a dynamic and ecologically grounded economy created by the guarantee of subsistence to all."
Keywords: Politics & government / bicssc; Basic income; Income distribution; Poverty